Radix Entomolaris and Complex Incisor Anatomy in a Saudi Cohort: A Retrospective Study - Mubashir Baig Mirza (Diagnostics, 2025)
Background/Objectives: A thorough understanding of tooth anatomy is essential for effective root canal treatment. This study aims to investigate the root canal morphology of mandibular incisors (MIs) and the presence of distolingual roots in mandibular first molars (MFMs) and to explore the potential correlation between these anatomical variations. Methods: A total of 562 CBCT scans were retrospectively analyzed, corresponding to 1124 mandibular central incisors (MCIs), mandibular lateral incisors (MLIs), and MFMs each. The DLR in MFMs was correlated with the complex anatomy in MIs and analyzed using a chi-square test, with the odds ratio obtained through binary regression analysis. Differences related to gender, site, and age were analyzed using the chi-square test. Results: Most MI scans revealed Vertucci Type I canal morphology, with a higher percentage in MCIs (71.1%) than MLIs (64.9%). Additionally, 5.25% of MFM scans indicated a DLR, with a higher prevalence in males (3.5%) and younger individuals (3.4%); however, a statistically significant difference was observed only in MCIs (p = 0.035) across different age groups. The study also identified a highly significant difference in complex canal anatomy, comparing both MIs on either side and the presence of DLR in MFMs (p < 0.001). Furthermore, the relationship between complex canal systems in MIs and MFMs with DLR was confirmed. Conclusions: In conclusion, the Vertucci Type I canal configuration was predominant in both MIs, followed by Type III. The DLR was present in 5.25% of the total scans, and its presence strongly correlated with complex morphology in both MIs.